Design and Build Web-Based Interactive Learning Media for Early Childhood in Early Childhood Kindergarten Mujahidin School - Fitri Laila; Ratnawati; Tatik Maslihatin; Febri Hidayat Saputra; Amran Amiruddin; Andi Yulia Muniar; Elmi; Benny Leonard Enrico Panggabean; Listia Utami; Muhammad Sabirin Hadis; Tamsir; Andi Nur Fadillah; Markani Pato; Asnimar Asnimar (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2026)
The problem faced by At The PAUD Mujahidin School In Barru Regency is that the learning process is still dominated by conventional methods so that it is less interesting and less effective in stimulating children's interest in learning. The solution offered is the development of web-based interactive digital media that contains learning materials, interactive quizzes, and learning outcome reports that can be accessed by teachers and principals. The aim of the study was to create learning media that is able to increase children's involvement, motivation, and learning outcomes. The data was obtained through  observation, interviews, library research and the distribution of questionnaires for feasibility tests. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The media is tested using Blackbox Testing to ensure system functionality as well as User Acceptance Test (UAT) to evaluate user satisfaction. The results of the study indicate  that 88% of respondents stated that this medium is very suitable for use, able to increase children's involvement, and provide a more enjoyable learning experience.